EDUKASI MENGGUNAKAN SOSIAL MEDIA DAN PELATIHAN BAGI KADER POSBINDU DALAM MENCEGAH DAN MENGENDALIKAN HIPERTENSI - Nurfitri Bustamam; Cut Fauziah; Pritha Maya Savitri (Universitas Majalengka, 2022)
As many as 80% of participants of Posbindu Delima RW 11, Sawangan Depok had hypertension. However, eight of the Posbindu Delima cadres had no educational background in the health sector, and only two cadres had received education about hypertension. The community service activities (CSA) were carried out for Posbindu Delima cadres to ensure that cadres have sufficient knowledge and skills to prevent and control hypertension in posbindu participants. Cadres were asked to fill out a pre-test questionnaire to measure their understanding of hypertension and show how to measure blood pressure. Then the cadres were trained to measure blood pressure correctly using a checklist. Education was given using WhatsApp in stages over two weeks. After that, the cadres were asked to fill out a post-test questionnaire. The results of these activities show that the level of knowledge and skills of cadres in measuring blood pressure increased significantly. Cadres also implement their knowledge to educate posbindu participants using WhatsApp and Instagram, as well as implement knowledge and blood pressure measurement skills in routine Posbindu activities. It can be concluded that this CSA has succeeded in increasing the competence of cadres in preventing and controlling hypertension.